Evaluation of geometrical defects in AWJM process of a hybrid CFRTP/ Steel structure - Bañón-García, Fermín; Sambruno, Alejandro; Batista, Moisés; Simonet, Bartolomé; Salguero, Jorge (Elsevier, 2021)
The bonding of Carbon Fibre Reinforced ThermoPlastic composites (CFRTP) and steel is of great interest nowadays. Nevertheless, the difference in machinability between dissimilar materials requires a specific machining process. Abrasive water jet machining is a flexible and environmentally friendly technology that can machine dissimilar materials at the same time with good results. However, due to the characteristics of the process and materials, geometrical defects such as taper angle can be caused by the loss of kinetic energy. In this research, the study of the final geometry in abrasive waterjet machining of a hybrid CFRTP/Steel structure. A new methodology for the evaluation of taper angle with high accuracy has been developed through image processing. In addition, the surface quality in terms of Ra and Rz has been assessed. A potential-type trend between taper and hydraulic pressure has been established for both materials. Minimum taper values between 1.5◦ and 5◦ have been obtained for both materials and stacking configurations with a combination of a hydraulic pressure of 420 MPa, an abrasive mass flow of 225 g/min and a traverse speed of 50 mm/min.
Keywords: Estructuras (Construcción) - Cálculo; Acero; Geometrical Defect; Taper Angle; AWJM; Machining; Hybrid Structure